Slavic Collectives in 6je - Matasović, Ranko (2005)
Slavic collective formations in 6je are derived from the PIE collective suffix *ey, discovered by Norbert Oettinger, and chiefly preserved in Greek and Hittite.
Projekt MZOS
ENG